Niestacjonalne przypadkowe pole temperatury i naprężeń w nieskończonym pręcie - Tylikowski, A.; Chmielniak, T. (Engineering Transactions, 1969)
The non-stationary temperature and stress field in an infinite bar contained in a medium, the temperature of which is a random phenomenon are considered within the frames of the correlation theory. The temperature field is determined by the value of the autocorrelation function kω (x1, x2, y1, y2) and the dispersion which are determined assuming constant coefficient of heat absorption. The correlation function and the dispersion of stresses is determined on the basis of the simplified deterministic problem [7].As an exaple of application a detailed solution is obtained for the temperature and stress field in a bar located in a gas stream leaving a combustion chamber assuming a sufficiently durable combustion process. In addition the problem of a stationary case is solved.